2004
DOI: 10.1073/pnas.0401896101
|View full text |Cite
|
Sign up to set email alerts
|

Short interfering RNA-mediated silencing of glutaredoxin 2 increases the sensitivity of HeLa cells toward doxorubicin and phenylarsine oxide

Abstract: Glutaredoxin (Grx) belongs to the thioredoxin fold superfamily and catalyzes glutathione-dependent oxidoreductions. The recently discovered mitochondrial and nuclear Grx (Grx2) differs from the more abundant cytosolic Grx (Grx1) by its higher affinity toward S-glutathionylated proteins and by being a substrate for thioredoxin reductase. Here, we have successfully established a method to silence the expression of Grx2 in HeLa cells by using short interfering RNA to study its role in the cell. Cells with levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 55 publications
5
100
0
Order By: Relevance
“…Depletion of mitochondrial GSH also potentiated peroxide accumulation and sensitized cells to cell death (8,157). Small interferring RNA (siRNA) for Grx-2 increased sensitivity to doxorubicin, whereas overexpression of mitochondrial Grx-2 inhibited cardiolipin loss and prevented apoptosis induced by doxorubicin (41,111). Because Trx and GSH protect against two-electron oxidants, this in vitro research points to the plausibility of oxidant-induce cell death mechanisms signaled by nonradical reactions, which disrupt redox control.…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%
“…Depletion of mitochondrial GSH also potentiated peroxide accumulation and sensitized cells to cell death (8,157). Small interferring RNA (siRNA) for Grx-2 increased sensitivity to doxorubicin, whereas overexpression of mitochondrial Grx-2 inhibited cardiolipin loss and prevented apoptosis induced by doxorubicin (41,111). Because Trx and GSH protect against two-electron oxidants, this in vitro research points to the plausibility of oxidant-induce cell death mechanisms signaled by nonradical reactions, which disrupt redox control.…”
Section: Oxidative Stress As a Disruption Of Redox Signaling And Controlmentioning
confidence: 99%
“…Previous studies (12,14) have revealed that GLRX2 is central in mitochondrial redox regulation. An RNA interference-induced GLRX2 knockdown sensitized mitochondria toward oxidative damage and apoptosis (12), indicating that GLRX2 could be an interesting intervention point in cancer therapy for sensitizing cells for apoptotic stimuli. It is conceivable that GLRX2 has several roles due to its enzymatic function in glutathionylation and deglutathionylation reactions.…”
Section: Structural Organization Of Dimeric Glrx2 Containing a [2fe-2s]mentioning
confidence: 99%
“…A further striking feature of GLRX2 is that it appears to be destined to function enzymatically primarily under oxidative conditions. First, high GSH/GSSG ratios will drive the GLRX2 equilibrium into a quiescent dimeric Fe-S-bound form (12,14), which can readily be activated as soon as the GSH/GSSG ratio drops under oxidative conditions. Second, GSH appears to be a direct inhibitor, as demonstrated by the non-productive complex of monomeric GLRX2 with reduced glutathione.…”
Section: Structural Organization Of Dimeric Glrx2 Containing a [2fe-2s]mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, knockdown of Grx2 sensitizes HeLa cells to anticancer drugs (63). A study indicated that Grx2 also has an anti-apoptotic function.…”
Section: Discussionmentioning
confidence: 99%